Extending the technology acceptance model to account for social influence, trust, and integration for pervasive computing environment: A case study in University Industri Selangor - Mohd, Farahwahida; Ahmad, Faudzi; Samsudin, Norsila; Sudin, Suhizaz (2010)
The aims of this study are to develop ubiquitous computing environment using Bluetooth (UCEB) and measure the validity and reliability on in order to support student admission services in Universiti Industri Selangor (UNISEL).This study is based on the descriptive survey research using revised Technology Acceptance Model(TAM), known as Pervasive Technology Acceptance Model (PTAM). This research involved all the aspects of PTAM which are namely perceived usefulness, perceived ease of use, social influence, trust, integration, attitude, behavioral intention and actual use towards using the UCEB. A total of 111 respondents were selected as a sample for this study.This research is also conducted on the same respondents to find out the user acceptance on UCEB to support student admission services. The respondents were the academic committees consist of students, academicians and non-academician of UNISEL. A questionnaire was used to collect information from the respondents based on Likert scale to measures the extent to which a person agrees or disagrees with the question.The quantitative data were analyzed using SPSS system to produce statistical inference for Pearson correlation test.